Evolutionary conservation of the grape sex-determining region in angiosperms and emergence of dioecy in Vitaceae - Mélanie Massonnet; Noé Cochetel; Valentina Ricciardi; Andrea Minio; Rosa Figueroa-Balderas; Jason P. Londo; Dario Cantu (Nature Communications)
Abstract In bunch grapes (Vitis spp.), flower sex is controlled by a ~ 200-kilobase sex-determining region (SDR) that contains genes involved in floral development. Here, we show that this region evolved from an ancient, highly conserved locus across angiosperms. Comparative genomic analysis of 56 plant genomes identifies homologous regions in all flowering plants but not in non-flowering lineages, suggesting a conserved role in floral function. Within the grape family (Vitaceae), we assemble and phase SDR haplotypes from six species, plus Leea coccinea as an outgroup, and find strong structural conservation, with size variation largely attributable to repetitive elements. Among the dioecious genera, Vitis and Muscadinia exhibit suppressed recombination in the SDR and share candidate sex-determining genes, whereas in Tetrastigma, the region appears to remain recombining, pointing to an alternative mechanism of sex determination. Altogether, our results suggest that dioecy emerged in grapes from a deeply conserved, collinear genomic region composed of multiple genes involved in floral development, morphology, and sexual fertility.